Impacts of using auto-mode portable air cleaner on indoor PM2.5 levels: An intervention study. (15th January 2021) - Huang, Ching-Hsuan; Xiang, Jianbang; Austin, Elena; Shirai, Jeff; Liu, Yisi; Simpson, Christopher; Karr, Catherine J.; Fyfe-Johnson, Amber L.; Kronborg Larsen, Thomas; Seto, Edmund
Abstract: "Auto-mode" portable air cleaners (PACs) designed to turn on automatically in response to elevated indoor PM2.5 concentrations are widely used in residences. This study assesses the impacts of using such PACs equipped with high-efficiency particulate air filters on residential PM2.5 levels in six households recruited in Seattle, Washington, for a randomized crossover study, in which participants used a PAC in their homes under three intervention scenarios: (1) sham-mode filtration in which all filters in the PAC were removed, (2) auto-mode filtration in which the PAC was set to auto mode, and (3) adjustable-mode filtration in which the participants were allowed to manually adjusted the PACs. Each filtration session was one-week long. PM2.5 levels were measured at 1-min intervals in the kitchen and living room of each household. Also, an hourly time-activity log was collected from each participant. The empirical concentrations and I/O ratios of PM2.5 were compared among the three filtration modes. Additionally, linear mixed-effects regression models (LMER) were developed to reveal the impacts of different filtration modes on indoor PM2.5, while controlling for outdoor PM2.5, indoor cooking events, and indoor relative humidity, and temperature. Based on the LMER models, when indoor cooking events were present and absent, auto-mode filtration significantly reduced the indoor PM2.5 levels by 31% [95% CI: 19%, 42%] and 28% [95% CI: 22%, 34%], respectively, compared with sham-mode filtration, and reduced the indoor PM2.5 levels by 19% [95% CI: 6%, 31%] and 4% [95% CI: 4%, 11%], respectively, compared with adjustable-mode filtration. These findings suggest that using such PACs running in auto mode is a practical and effective way to reduce indoor PM2.5 levels. Highlights: A randomized crossover study was conducted in six US households for three weeks. The impacts of multimode air cleaner filtration on indoor PM2.5 were evaluated. Empirical data (concentration, I/O ratio) were compared among the filtration modes. Models were developed to show the impacts after adjusting for the main factors. Air cleaner running in auto mode resulted in the lowest indoor PM2.5 concentrations.